HAK-HAK SEORANG NARAPIDANA SEBAGAI PEKERJA DI LEMBAGA PEMASYARAKATAN KELAS II A PEKANBARU - Putri Sanaya; Maryati Bachtiar; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Being in the correctional system, convicts have obligations that they must carry outand rights that must be fulfilled by the state. These rights and obligations are outlined in LawNumber 12 of 1995 concerning Corrections and Menkum HAM Regulation Number 6 of 2013concerning Rules of Correctional Institutions and State Detention Centers. This researchexamines the rights of an inmate as a worker in the Pekanbaru Class II A CorrectionalInstitution and the fulfillment of the rights of an inmate as a worker in the Pekanbaru Class IIA Correctional Institution.This type of research can be classified as sociological, because in this study theauthor directly conducts research at the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted at thePekanbaru Class II A Penitentiary, while the population and sample were all parties relatedto the problems studied in this study, the data sources used were primary data, secondarydata, and tertiary data, data collection techniques in this study were observation, interview,questionnaire, and literature study.From the results of the study, it can be concluded that the rights of convicts asworkers in Class II A Penitentiary in Pekanbaru have not been carried out optimally, one ofwhich is the absence of guarantees for work safety, because the work provided does not havea high risk and the tools used in work are safe . Nevertheless, convicts should have the rightto work safety guarantees. Second, convicts who take part in the apprenticeship do not get apremium. Even so, some of the rights of convicts as workers have been implemented.Furthermore, convicts working at the Pekanbaru Class II A Penitentiary already know whattheir rights are, so this is also one of the transparent information for convicts about the rightsthey should receive. Second, the suggestion according to the author is that the governmentshould stipulate regulations or laws that regulate in detail the large percentage of wages thatconvicts are entitled to receive as well as adding more tutors/guidance trainers so that theycan match the number of convicts attending training..Keywords: Rights, Prisoners, Workers